PENDIDIKAN MULTIKULTUR DALAM AKTIVITAS KEAGAMAAN DI KONCO PURA TAMAN GANDASARI DESA DANGIN PURI KAJA KECAMATAN DENPASAR UTARA PROVINSI BALI - Astajaya, I Ketut Manik; Erna Tanu Ria Sari, Ni Made Ayu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2021)
Konco Pura Taman Gandasari is not only a place of worship for Tri Dharma Buddhists but also as a place of worship for Hindus. As is well known, tolerance between Hindus and Buddhists at Konco Pura Taman Gandasari can be used as an example of unity that produces harmony among others. Basically, the tolerance practiced by these people in responding to differences in beliefs and beliefs is a term in a social, cultural and religious context which means attitudes and actions that prohibit discrimination against different groups. This research generally aims to describe and to know comprehensively about the Konco Pura Taman Gandasari in a multicultural dimension so that it becomes the foundation of diversity into the realization of harmony in religious, national and state life and the willingness to understand, appreciate, acknowledge and accept diversity which has become a social reality. Indonesian people know that Bhinneka Tunggal Ika community which has a diversity of tribes, cultures, religions, languages, and others. However, there is one thing that still and really needs to be formed through multicultural education and an understanding of cultural relativity by growing a sense and awareness of the importance of respecting, acknowledging, and accepting existing diversity. The presentation of data analysis in this study begins with the data collection process. After collecting data on Multicultural Education in Religious Activities at Konco Pura Taman Gandasari, the data was compiled systematically and analyzed in the data reduction process. After the data reduction process, the results of the data analysis were presented using a descriptive method. If it is valid, then it is described and a comprehensive conclusion is obtained about the structure, function and characteristics of multicultural education in Multicultural Education in Religious Activities at Konco Pura Taman Gandasari.